Financial Management and Business Communication Training for Micro Business Unit Owners - Sri Nathasya Br Sitepu; Monika Teguh; Deandra Vidyanata; Helena Sidharta (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Abstract Pakal sub-district micro business owners experience limited knowledge to manage finances and business communication. This limitation hinders the growth of micro businesses to develop into small to medium businesses. The problem of micro business owners is overcome through community service activities in the form of financial management and business communication training. The objectives of the training include: 1) providing entrepreneurship knowledge, 2) providing knowledge of financial management concepts and practices, 3) improving communication science to the ability to practice business communication. The training motto was given to partners (housewives who own micro businesses) in the amount of 10 people. The training was carried out offline. Training activities consist of three stages, namely: observation, training and evaluation. The results of the training activities of participants/partners (housewives who own micro businesses) have increased their knowledge of entrepreneurship, financial management and knowledge of communication science. The training succeeded in improving participants' soft skills in the form of financial management practices and business communication with micro business partners. The implication is that the quality of partners (housewives) increases in the management of micro businesses. Pemilik usaha mikro kecamatan Pakal mengalami pengetahuan yang terbatas untuk mengelola keuangan dan komunikasi bisnis. Keterbatasan ini menghambat pertumbuhan usaha mikro untuk berkembang menjadi usaha kecil hingga menengah. Permasalahan pemilik usaha mikro diatasi melalui kegiatan pengabdian masyarakat berupa pelatihan manajemen keuangan dan komunikasi bisnis. Tujuan dari pelatihan meliputi: 1) memberikan pengetahuan kewirausahaan, 2) memberikan pengetahuan tentang konsep dan praktik manajemen keuangan, 3) meningkatkan ilmu komunikasi hingga kemampuan mempraktikkan komunikasi bisnis. Motto pelatihan diberikan kepada mitra (ibu rumah tangga yang memiliki usaha mikro) sebesar 10 orang. Pelatihan dilakukan secara luring. Kegiatan pelatihan terdiri dari tiga tahap, yaitu: observasi, pelatihan dan evaluasi. Hasil kegiatan pelatihan peserta/mitra (ibu rumah tangga yang memiliki usaha mikro) telah meningkatkan pengetahuan mereka tentang kewirausahaan, manajemen keuangan dan pengetahuan ilmu komunikasi. Pelatihan berhasil meningkatkan soft skill peserta berupa praktik pengelolaan keuangan dan komunikasi bisnis dengan mitra usaha mikro. Implikasinya kualitas mitra (ibu rumah tangga) meningkat dalam pengelolaan usaha mikro.